Assessment of nutritional status of rotating shift workers of community support brigade and university police force in the University of the Philippines, Los Baños, Laguna - Bencito, Shekinah Ginel C.; Bernardo, Aiza Kris M. (2019)
The health and well-being of shift workers have continuously deteriorated due to the increasing demand for their services. Given that nutrition is a component of overall health, the lack of proper nutrition among shift workers who render services through physical work may put their health at risk, affecting work productivity. This study assessed the nutritional status of rotating shift workers employed as part of the Community Support Brigade (CSB) and University Police Force (UPF) at the University of the Philippines Los Baños (UPLB) in Laguna, Philippines. Respondents (n=57) wereprofiled based on their socio-demographic and socio-economic profile, nutrition- and lifestyle-related behaviors, and anthropometric measurements. Dietary habits and food intake were also assessed. Findings showed high prevalence of obesity (63%) among respondents based on WHO BMI cut-off points for adults. Majority of respondents also usually skip meals, have poor sleep quality, are current smokers, consume alcoholic beverages, and have sedentary lifestyle. Although consumption of a va- riety of foods was observed, the usual intakes of fried and fatty foods were high. The average nutrient adequacy level was not met for most nutrients. The study concluded that rotating shift work poses negative effects on the health and nutritional status of workers. Nutrition education on maintaining proper weight through healthy dietary and lifestyle habits may help improve the nutritional status and overall health of shift workers. Moreover, it is imperative to provide them with a healthy environment.
Keywords: Nutritional status